Pengaruh Keselamatan Kerja, Kenyamanan Kerja, dan Kesehatan Lingkungan Kerja Terhadap Kinerja Karyawan pada PERUMDA Tirta Moedal Kota Semarang - Abdillah, Wimbo; Oktavia, Vicky; Subagyo, Herry; Febriana, E Artha (Jurnal EMT KITA, 2024)
This research aims to analyze the influence of workplace safety, comfort, and environmental health on employee performance. A quantitative method was employed in this study. The sampling method used was probability sampling, with a total of 381 employees and 90 respondents serving as the research sample. Data were collected through the distribution of questionnaires. SPSS version 25 was used to analyze the data. Based on the results of multiple linear regression data analysis, the findings indicate that workplace safety and comfort have a significant effect on employee performance, while environmental health has a positive but not significant effect on employee performance.